OBTAINING OF AMPHIPHILIC LIGNIN POLYMERS - Mitina , Nataliya; Harhay , Khrystyna; Izhyk , Oleh; Zaichenko , Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2025)
In our proposed method, lignin is modified by grafting functional polymers and copolymers via radical polymerization, initiated by a redox system involving Ce(IV) salts and lignin's hydroxyl groups. Lignin’s aliphatic hydroxyl groups act as reducing agents, generating radicals necessary for the polymerization of N-vinylpyrrolidone and glycidyl methacrylate. Branched copolymers were synthesized by reacting the epoxy groups of modified lignin with the hydroxyl groups of polyethyloxazoline in the presence of boron trifluoride etherate. Polymer grafting was successfully confirmed through elemental analysis, FTIR and NMR spectroscopy.